ATCA 16 cm observation of CIZA J1358.9−4750: Implication of merger stage and constraint on non-thermal properties. (18th May 2018) - Akahori, Takuya; Kato, Yuichi; Nakazawa, Kazuhiro; Ozawa, Takeaki; Gu, Liyi; Takizawa, Motokazu; Fujita, Yutaka; Nakanishi, Hiroyuki; Okabe, Nobuhiro; Makishima, Kazuo
Abstract: We report the Australia Telescope Compact Array 16 cm observation of CIZA J1358.9−4750. Recent X-ray studies imply that this galaxy cluster is composed of merging, binary clusters. Using the EW367 configuration, we found no significant diffuse radio emission in and around the cluster. An upper limit of the total radio power at 1.4 GHz is ∼1.1 × 10 22  W Hz −1 in 30 square arcminutes, which is a typical size for radio relics. It is known that an empirical relation holds between the total radio power and X-ray luminosity of the host cluster. The upper limit is about one order of magnitude lower than the power expected from the relation. Very young (∼70 Myr) shocks with low Mach numbers (∼1.3), which are often seen at an early stage of merger simulations, are suggested by the previous X-ray observation. The shocks may generate cosmic-ray electrons with a steep energy spectrum, which is consistent with non-detection of bright (>10 23  W Hz −1 ) relic in this 16 cm band observation. Based on the assumption of energy equipartition, the upper limit gives a magnetic field strength of below 0.68 f ( D los /1 Mpc) −1 (γmin /200) −1  μG, where f is the cosmic-ray total energy density over the cosmic-ray electron energy density, D los is the depth of the shock wave along the sightline, and γmin is the lower cutoff Lorentz factor of the cosmic-ray electron energy spectrum.